Pemeriksaan Kesehatan Lansia Dhuafa Binaan Pimpinan Wilayah Aisyiyah Provinsi Kalimantan Timur - Tri Wahyuni; Fitroh Asriyadi; Andi Fatmawati Syamsu (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The poor elderly are people aged 60 years and over, who experience socio-economic problems so they do not carry out their health checks due to limitations. This community service aims to detect health problems early in elderly poor people who have difficulty accessing health facilities due to their limitations. This early detection of health is carried out free of charge with the aim of helping poor elderly people who cannot carry out health checks due to various obstacles, held at the Siti Khadijah Orphanage, Jalan Merdeka Samarinda, on September 24, 2022. Participants in the detection of health problems consisted of 51 elderly people, checking their blood pressure, weight, height, current blood sugar, uric acid, and cholesterol. From this examination, the highest number of participants were the elderly as much as 90.2%, the elderly who were detected to have high blood pressure as much as 60.8%, had diabetes mellitus as much as 21.6%, had high cholesterol levels based on sex as much as 35.3%, and who experienced hypercholesterolemia as much as 43.1%, and 45.1% who are obese.